2015 IEEE Eighth International Conference on Software Testing, Verification and Validation Workshops (ICSTW) 2015
DOI: 10.1109/icstw.2015.7107435
|View full text |Cite
|
Sign up to set email alerts
|

A first systematic mapping study on combinatorial interaction testing for software product lines

Abstract: Software Product Lines (SPLs) are families of related software systems distinguished by the set of features each one provides. Over the past decades SPLs have been the subject of extensive research and application both in academia and industry. SPLs practices have proven benefits such as better product customization and reduced time to market. Testing SPLs pose additional challenges stemming from the typically large number of product variants which make it infeasible to test every single one of them. In recent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 68 publications
(38 citation statements)
references
References 46 publications
0
38
0
Order By: Relevance
“…Since typical HCSs can have thousands or even millions of different configurations, several sampling techniques have been proposed to reduce the number of configurations to be tested (e.g. [46,50,55]). Salient among them is pairwise testing whose goal is to select test suites that contain all possible combinations of pairs of features [46].…”
Section: A C C E P T E D Mmentioning
confidence: 99%
See 2 more Smart Citations
“…Since typical HCSs can have thousands or even millions of different configurations, several sampling techniques have been proposed to reduce the number of configurations to be tested (e.g. [46,50,55]). Salient among them is pairwise testing whose goal is to select test suites that contain all possible combinations of pairs of features [46].…”
Section: A C C E P T E D Mmentioning
confidence: 99%
“…[46,50,55]). Salient among them is pairwise testing whose goal is to select test suites that contain all possible combinations of pairs of features [46]. As an example, Table 3 shows the set of configurations obtained when applying pairwise testing to the model in Figure 1.…”
Section: A C C E P T E D Mmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, a mapping study published by Lopez-Herrejon et al (2015) reported that numerous works have been done on Combinatorial Interaction Testing in SPL, by looking from two perspectives which is what phase and how phase of CIT. Similar to our work, they also presented state-of-the-art works based on the techniques employed in CIT.…”
Section: Related Workmentioning
confidence: 99%
“…A number of researchers had proposed a couple of prominent strategies to reduce the combinatorial explosion of feature configuration testing [6]. Based on our literature, most of the current approaches are based on greedy algorithms with only a few works leveraged the potential of search-based techniques, which have been widely used in the single software development testing.…”
Section: Introductionmentioning
confidence: 99%